Peran Guru Patimpus dalam Dinamika Pembentukan Kota Medan: Perspektif Sejarah Sosial dan Budaya - Saragih, Ahmad Rifki; Prasetyo, Agung; Wahyuningsi, Tri; Siregar, Yusra Dewi (Medan Resource Center, 2024)
This study explores the foundational role of Guru Patimpus in the establishment and development of Medan City, tracing its origins from the initial land clearing at the Deli and Babura Rivers to its evolution as a major metropolitan area in Indonesia. The research investigates how Guru Patimpus, as the ruler of the Kedatukan Urung Sapuluh Dua Kuta Hamparan Perak, established Kampung Medan and facilitated cultural and trade exchanges between the highland and lowland communities. Employing qualitative literature review methods, this research highlights the contributions of Guru Patimpus and the subsequent influences of the Aru Kingdom, Sultanate of Deli, Langkat, and Asahan, which collectively shaped Medan’s growth. The study concludes that Guru Patimpus's actions were pivotal in establishing Medan’s role in regional trade and cultural integration, positioning it as a significant historical and cultural center.